Comparative Analysis of Labour Migration’s Impact on Demographics in Moldova and the Czech Republic - Volcov, Daniil (2025)
This thesis examines labor migration between Moldova and the Czech Republic, analyzing the economic and demographic impacts on both countries. It applies migration theories to understand the factors driving migration, such as labor demand in the Czech Republic and limited economic opportunities in Moldova. The study includes regression analysis of Moldovan emigration, showing that higher wages and remittances reduce emigration, while inflation increases it. The Czech Republic's migration trends, however, are not significantly explained by economic variables. The findings provide insights into labor migration's role in shaping both countries' economies and offer recommendations for policymakers.